Multi-method evaluation of a national clinical fellowship programme to build leadership capacity for quality improvement. Issue 4 (14th October 2020) - Toma, Madalina; Blamey, Avril; Mahal, Dawn; Gray, Nicola M; Allison, Laura; Thakore, Shobhan; Bowie, Paul
Abstract : Background: This paper reports the results of the evaluation of the Scottish Quality and Safety Fellowship (SQSF)—a 10-month, lead-level international educational programme established in 2008 with the overarching aim of developing clinicians with advanced quality improvement knowledge, technical ability and essential leadership skills. The evaluation explores four levels of educational and practice outcomes associated with (1) the reaction of fellows to SQSF participation, (2) learning gained, (3) subsequent behaviour changes and (4) the overall impact on national and international level capability and capacity building. Methods: A theory-informed multi-method design was applied using (1) a search and review of the SQSF organisational database to tabulate personal, professional and demographic characteristics; (2) semi-structured telephone interviews with 16 participants using purposive and self-selected sampling; and (3) a cross-sectional online evaluation survey across all 10 cohorts involving 222 fellows Results: SQSF was positively perceived as a high-quality learning experience containing a well-balanced mix of theory and practice, with a majority of respondents reporting career changing benefits. Most participants reported improved social, behavioural and emotional skills, knowledge and attitudes and, with sustained support of their host organisations, were able to apply and share learning in their workplace. The impact of the SQSF on a wider national and international level capability and capacity was both mediated and moderated by a wide range of interrelated contextual factors. Conclusions: This multi-method evaluation demonstrates that SQSF has achieved significant positive outcomes for the great majority of participants. Some tentative recommendations are provided with the aim of further enhancing fellowship content, delivery, transfer and future evaluations of wider impacts at regional, national and international health system levels.